A closer look at aortic seat belt injuries: review of 52 cases published in the last 60 years
INTRODUCTION: Seat belt aorta is a rare but often severe complication arising from blunt trauma with compression of the abdominal aorta against vertebrae. Seat belt sign is often present as an ecchymosis across the abdomen. The association with abdominal wall disruption and hollow viscus injury has been named seat belt triad; the presence of Chance fracture is sometimes considered a fourth component. METHODS: Using Pubmed and Embase databases we reviewed all articles regarding abdominal seat belt aortic injuries and analysed presentation at admission, concomitant lesions, including presence of seat belt triad, treatment and outcomes. RESULTS: Fifty-two cases were reported, from 1968 to 2019. Twenty-nine males (56%), mean age 43 ± 19 years. Most patients were stable at admission, with 29 (55.8%) presenting acute abdomen, 26 (50%) limb ischemia, 9 (17.3%) hypovolemic shock and 2 (3.8%) late-onset claudication. Seat belt sign was identified in 40 patients (76.9%), seat belt triad in 38 (73.1%) and 22 (42.3%) had Chance fractures, of which only 2 were not associated with seat belt triad. Most patients presented with aortic dissection (90.4%), complicated with pseudoaneurysm (11.5%), contained rupture (7.7%) or uncontained rupture (3.8%); 2 patients presented isolated iliac thrombosis and 3 limb ischemia. All patients required immediate surgical intervention, of which 40 (76.9%) required urgent vascular surgery. Forty-eight patients (92.3%) underwent vascular surgery: 39 open revascularizations and 9 endovascular procedures; three were managed conservatively. Ten patients (19.2%) passed away or died, of which 7 had seat belt triad. No patients needed reinterventions for vascular lesions except one, yet 3 required limb amputation. Most patients with seat belt triad required further visceral and abdominal wall repair. CONCLUSIONS: Seat belt aorta and especially seat belt triad are severe complications associated with high morbimortality often requiring surgery and multiple interventions. As patients are usually conscious and stable upon admission, this condition should not be disregarded.